IDENTIFIKASI FAKTOR YANG BERPENGARUH TERHADAP KINERJA WAKTU PELAKSANAAN PROYEK PENGADAAN TRANSMISI 500KV SUMATERA - Burhanuddin Robbani (Racic : Rab Construction Research, 2019)
The construction of the 500 kV Sumatra transmission network is the main project supporting the transmission line below and first on the island of Sumatra. With the Engineering, Procurement, and Construction (EPC) project scheme in its implementation the main contractor experienced several technical and non-technical constraints that affected the time performance of the project itself. This study aims to identify the factors that influence the performance of the project implementation time from the pre-construction stage (licensing, land clearing, and design planning) to the construction of the construction. The research method used is a survey method of the Project Implementation Unit with analysis using the Relative Importance Index (RII) method. The results showed that factors related to licensing problems from the government, inaccurate survey data (Pre-Design), and scarcity of raw materials are the three main problems that affect the performance time of the Sumatra 500 kV transmission development project